Sistem Pemerintahan dan Implementasi Kebijakan Pendidikan: Kajian Literatur di Amerika Serikat, Jerman, dan China - Mujiono Mujiono; Dedi Kuswandi; Agus Wedi (LPPM Press, 2026)
This study aims to explore the relationship between governance systems and the implementation of education policies in three countries with different governance characteristics: the United States (federal), Germany (federal-parliamentary), and China (centralized). The study employs the Systematic Literature Review (SLR) method to examine relevant literature on education policies and governance systems in these three countries. Data were collected and analyzed to evaluate the design and implementation of education policies. The analysis revealed that the federal governance systems in the United States and Germany provide flexibility for local governments to adapt policies to local needs, although this creates variations in education quality and access across regions. Conversely, China's centralized system ensures uniform policy implementation but faces challenges in meeting local needs, particularly in rural areas. Policies such as the Education Act (US), BAföG (Germany), and Education Law (China) reflect how governance systems influence the design and implementation of education policies. The findings indicate that a centralized approach is more effective for consistency, while a decentralized approach is more flexible in accommodating local needs. This study provides insights that optimizing governance systems in education policies requires balancing centralization for consistency and decentralization for flexibility to enhance policy effectiveness.